2010
DOI: 10.1016/j.lfs.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Intrahippocampal injection of TsTX-I, a beta-scorpion toxin, causes alterations in electroencephalographic recording and behavior in rats

Abstract: The results suggest that TsTX-I toxin may be responsible, at least in part, for the epileptic and behavioral effects observed with the crude venom, and although veratridine and TsTX-I act on Na-channel, the differences between them are remarkable, demonstrating that toxins can have different functional effects depending on the site of action in the channel. Thus, animal neurotoxins are often highly selective and may be useful for the identification of the sequence of events underlying neurotransmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The very little spectrometric and spectroscopic information allowed us to propose a generic structure of IIA-2-2. in rats and mice (Nencioni et al, 2000;Lourenço et al, 2002;Cunha et al, 2005;Teixeira et al, 2010;Caliskan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The very little spectrometric and spectroscopic information allowed us to propose a generic structure of IIA-2-2. in rats and mice (Nencioni et al, 2000;Lourenço et al, 2002;Cunha et al, 2005;Teixeira et al, 2010;Caliskan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the BmK I, an alpha-like scorpion neurotoxin isolated from the venom of Buthus martensi Karsch, induced seizures in rats by intrahippocampal administration (Bai et al 2006). Moreover, the TsTX-I, a scorpion neurotoxin isolated from T. serrulatus venom, promoted short and long epileptic-like discharges when injected in the hippocampus of rats (Teixeira et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Because Serrumab was able to inhibit $50% of the effect of the major toxin, we can presume that it would counter some effects of scorpion envenomation. Other authors have shown that Ts1 plays an essential role in envenomation (Bertazzi et al, 2003;Correa et al, 1997;Teixeira et al, 2010;Vasconcelos et al, 2005).…”
Section: Discussionmentioning
confidence: 96%